Transformasi Kewenangan Bawaslu dalam Sistem Penegakan Hukum Pemilu Pasca Putusan MK No. 104/PUU-XXIII/2025 [Transformation of Bawaslu’s Authority in the Election Law Enforcement System Post Constitutional Court Decision No. 104/PUU-XXIII/2025] - Prandy Arthayoga Louk Fanggi; Nakzim Khalid Siddiq (Indonesia Berdaya, 2026)
Elections are the primary instrument for implementing popular sovereignty within Indonesia’s constitutional democratic system. However, the dynamics of election administration still face various challenges such as administrative violations, vote buying, and weak effectiveness in election law enforcement. This study aims to analyze the transformation of the Election Supervisory Agency’s (Bawaslu) authority following the Constitutional Court Decision Number 104/PUU-XXIII/2025, which changed Bawaslu’s recommendations into final and binding decisions. Using a normative juridical research method with legislative, conceptual, and case approaches, this study finds that the Court’s decision brings significant changes to Indonesia’s electoral justice system. First, it strengthens Bawaslu’s position as a quasi-judicial institution with adjudicative functions in election law enforcement. Second, it affirms the principle of checks and balances among election administrators. Third, it enhances legal certainty and accountability in the administration of democratic and integrity-based elections. Nevertheless, the effectiveness of this transformation still depends on regulatory harmonization, institutional reform, and capacity building of Bawaslu personnel at all levels. Abstrak. Pemilihan umum merupakan instrumen utama pelaksanaan kedaulatan rakyat dalam sistem demokrasi konstitusional Indonesia. Namun, dinamika penyelenggaraan pemilu masih menghadapi berbagai pelanggaran administratif, politik uang, serta lemahnya efektivitas penegakan hukum kepemiluan. Penelitian ini bertujuan untuk menganalisis transformasi kewenangan Badan Pengawas Pemilu (Bawaslu) pasca Putusan Mahkamah Konstitusi Nomor 104/PUU-XXIII/2025 yang mengubah status rekomendasi Bawaslu menjadi putusan yang bersifat final dan mengikat. Dengan metode penelitian yuridis normatif melalui pendekatan perundang-undangan, konseptual, dan kasus, penelitian ini menemukan bahwa Putusan MK tersebut membawa perubahan signifikan terhadap sistem electoral justice di Indonesia. Pertama, memperkuat kedudukan Bawaslu sebagai lembaga quasi-judicial yang memiliki fungsi adjudikatif dalam penegakan hukum pemilu. Kedua, menegaskan prinsip checks and balances antarpenyelenggara pemilu. Ketiga, meningkatkan kepastian hukum serta akuntabilitas dalam penyelenggaraan pemilu yang demokratis dan berintegritas. Meskipun demikian, efektivitas transformasi ini masih bergantung pada harmonisasi regulasi, reformasi kelembagaan, serta peningkatan kapasitas aparatur Bawaslu di seluruh tingkatan.